Catalytic depolymerization of cellulose to nanocellulose using heteropoly acid / Siti Khadijah binti Zain - Zain, Siti Khadijah (2015)
Heteropoly acid (HPA) and its acidic salts have been widely applied as catalysts for various types of chemical reactions. The substitution process involving proton with larger monovalent alkaline cation (cesium) within the Keggin structure has tremendously affected the microstructure of heteropoly compounds. Generally, higher content of cesium (Cs), posses higher surface area and porosity. Nevertheless, low cesium content of heteropoly compound was selected for better hydrolysis environment in depolymerization of cellulose. This is because, none or low cesium content of Heteropoly compound can generate high concentration of hydronium ions when dissolved in water. That characteristic has increased the possibility of proton to hydrolyze the - linkages of cellulose polymer chain. Heteropoly acid and its acidic salts were screened for their performance towards depolymerization of cellulose to nanocrystalline cellulose (NCC) with the assistance of powerful ultrasonication. Ultrasonication treatment introduced has enhanced the depolymerization of cellulose through defibrillation of cellulose polymer chain, which eases the function of HPA catalyst. Ionizable proton generates from HPA can easily penetrate the amorphous region of cellulose thus release the crystalline domain. The generated NCC were analyzed by Fourier Transform Infrared (FTIR), X-ray Diffraction (XRD) , Raman spectroscopy, Dynamic Light Scattering (DLS), Zeta potential, Surface Tension, Thermogravimetric analysis (TGA), Scanning Electron Microscope (SEM), Transmission Electron Microscope (TEM), and Atomic Force Microscopy (AFM). The results from the material characterization revealed that when HPA was applied as a catalyst, the treatment time was reduced by 5 minutes and the crystallinity index (CrI) calculated through XRD analysis was 88.0 %, similarly when the reaction was carried out at 15 minutes in the absence of HPA catalyst. Furthermore, the smallest particle sizes obtained was 37.84 nm and 43.82 nm with the presence and absence of HPA respectively. However, TEM images of NCC showed some agglomeration and accumulation of cellulose particles thus indicating that the particles are highly attracted to each other due to surface hydrophilicity. From the TEM images, the diameter measured was at range of 10-30 nm. Therefore, this study shows that the choices of appropriate hydrolysis condition in producing NCC are very crucial and important. For that reason, the best reaction condition for obtaining NCC were discovered at 225 W (ultrasonication) for 10 minutes with the presence of 4 g of Tungstophosphoric acid (TPA) catalyst. Therefore, it shows that HPA is one of the best alternatives in replacing classical sulfuric acid in hydrolysis of cellulose to nanocrystalline cellulose (NCC).